PERAN TEKNOLOGI INFORMASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Harahap, Heeppy Haryadi; Anggriani, Riska; Ayu, Anggun Putri (LPPM Universitas Muhammadiyah Jambi, 2024)
Information technology plays a key role in economic growth, especially in the era of industry 4.0 and towards 5.0. Technological innovation is changing the way people communicate and do business, with the internet being a key indicator of progress. However, Indonesia faces challenges in the implementation of information technology, including cybersecurity, global competition, human resource development, uneven internet access, and outdated regulations. Research shows that the use of information and communication technology has a positive contribution to national income, boosts productivity, and creates new jobs. Thus, the role of information technology in Indonesia's economic growth is an area that needs more attention in the face of global dynamics